A panel of protein markers for the early detection of lung cancer with bronchial brushing specimens. Issue 11 (9th July 2014) - Liu, Yi‐Zhen; Jiang, Yan‐Yi; Wang, Bo‐Shi; Hao, Jia‐Jie; Shang, Li; Zhang, Tong‐Tong; Cao, Jian; Xu, Xin; Zhan, Qi‐Min; Wang, Ming‐Rong
<x xml:space="preserve">Abstract</x> BACKGROUND To date, no robust biomarkers have been available in clinical practice that can provide an early diagnostic evaluation of lung cancer. The objective of this study was to identify potential biomarkers for the early detection of lung cancer using bronchial brushing specimens. METHODS Immunocytochemistry was used to investigate the expression of 35 proteins in 880 bronchial brushing specimens from both outpatients and inpatients who had either lung cancer or benign lung lesions. An optimal panel was identified that had high sensitivity and considerable specificity for detecting lung cancer. Associations between protein expression and clinicopathologic parameters were assessed. RESULTS Tumor protein 53 (TP53), TP63, Ki67, epidermal growth factor receptor (EGFR), minichromosome maintenance complex component 6 (MCM6), MCM7, uncharacterized proteins KIAA1522 and KIAA0317, and ubiquitin‐protein ligase UHR1 (ICBP90) frequently presented high expression in bronchial brushing specimens from patients who had lung cancer compared with patients who had benign lung lesions. A 6‐protein panel consisting of TP53, Ki67, MCM6, MCM7, KIAA1522, and KIAA0317 was identified as the best combination, with sensitivity of 81.1% (309 of 381 specimens) for detecting nonsmall cell lung cancer (NSCLC) and 86.8% (145 of 167 specimens) for detecting small cell lung cancer (SCLC) (specificity, 83.3%; 65 of 78 specimens). The combination of cytology and the protein panel significantly improved the sensitivity of bronchial brushing examination for detecting lung cancer (P<.00001), which increased from 49.1% to 81% in early stage NSCLC (stage I and II). In combined analyses, the protein panel was positively associated with patient sex (P=.00033), tumor type (P<.00001), tumor location (P<.00001), and lymph node metastasis (P=.028). CONCLUSIONS The 6‐protein panel is a potential biomarker for the early detection of lung cancer in bronchial brushings. Cancer (Cancer Cytopathol) 2014;122:833–841. © 2014 American Cancer Society.